Biocompatible Delivery System for Metformin: Characterization, Radiolabeling and In Vitro Studies - Aydın, Burcu; Uçar, Eser; Tekin, Volkan; İçhedef, Çiğdem and Teksöz, Serap (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: In recent years, the uses of nanotechnology in medicine have an increasing potential as an effective nanocarrier system. These systems are improved with the purpose of maximizing therapeutic activity and minimizing undesirable side-effects. Moreover, radiolabeled nanoparticles can be used as agents for diagnosis and therapeutic purposes in clinical applications. They have three main components: the core, the targeting biomolecule, and the radionuclide. Objective: It is aimed to synthesize Metformin (MET) loaded Solid Lipid Nanoparticles (MET-SLN) and radiolabeled with technetium-99m tricarbonyl core. Methods: The structure of synthesized nanoparticles was characterized by Fourier Transform Infrared Spectroscopy (FTIR). The particle size and morphology of nanoparticles were examined by Dynamic Light Scattering (DLS), and Scanning Electron Microscope (SEM). Quality control studies of radiolabeled MET-SLN [99mTc(CO)3-MET-SLN] were performed by High-Performance Liquid Radiochromatography (HPLRC) and Thin Layer Radiochromatography (TLRC). Results: The radiolabeling yield of [99mTc(CO)3-MET-SLN] was found to be 88%. In vitro studies have been performed on cancer lines(MCF7, MDA-MD-231 breast, and HEPG2 liver cancer cells) to determine the biological behavior of 99mTc(CO)3-MET-SLNs. Conclusion: The results showed that higher uptake values were observed on estrogen-positive MCF7 breast cancer cell line according to estrogen negative MDA-MB-231 breast cancer and HEPG2 liver cancer cell lines.
Keywords: Metformin